Comparative analysis of different microinsurance delivery models in Metro Manila - Delegencia, Cindy Mae G., Domingo Raphael Andre D., Guerrero, Andrew Jade E., Miranda, Stephanie Angela G., Romance, Fria Isabel E. 4 0 16; 5 (2023)
Abstract Microinsurance is protection for low-income individuals against certain risks and different types of delivery models were used in delivering microinsurance products to its target market. The microinsurance delivery models have different types, which are the Partner-Agent model, the Community-Based Organisation, the Full-Service model, and the Provider model. This research focuses on the comparison of delivery models used by the microinsurance companies in Metro Manila and aims to discover the challenges that consumers experienced regarding the delivery of microinsurance products and their accessibility. The study analyzes the net sales of three specific companies to see who is superior among the three in terms of a higher amount of net sales, one company per sector which are the Life sector, Non-Life sector, and Mutual Benefit Association. The analyzed data consist of respondents' experiences in terms of applying, paying, and claiming for their policies. To answer the question of challenges and accessibility, the researchers used survey questionnaires to gather and analyze data. The findings revealed that the superior model is a Hybrid of Partner-Agent and Full Service and got the highest rank in the base in their net sales. It also revealed that high-interest rate is the most challenging that customers have experienced, and Micro-Finance Institution (MFI) is one of the ways to access microinsurance products. By comparing the microinsurance delivery models, the researchers tend to give improvement points on every model that the companies utilize in Metro Manila.
Research Paper: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2